Sexual dimorphism in tooth morphometrics: An evaluation of the parameters - Abhishek Banerjee; Venkatesh Kamath; Krishnanand Satelur; Komali Rajkumar; Lavanya Sundaram (Journal of Forensic Dental Sciences, 2016)
Aims and Objectives: Sexual dimorphism refers to the variations in tooth size and shape between the sexes. The consistency of these variations is valuable in the identification of the sex of an individual in times of mass disaster when whole body parts get destroyed or are unavailable. There exist differences in the expression of these variables across races and regions. This study aims to tabulate and identify the variations in tooth measurements using standarized reference points in an attempt to establish parameters of sexual dimorphism. Materials and Methods: 100 individuals (50 of each sex) in the age group 19-23 years were assessed for standard morphometric parameters of the maxillary central incisor, canine, premolar and molar. Odontometric measurements of established parameters were recorded from impression casts of the maxillary jaws. The mesiodistal width (MDW), the bucco-ligual width (BLW), the crown length (CL) and the cervical angle (CA) were charted among the teeth. The consistency of the variations was statistically analyzed and a logistic regression table was prepared to identify the sex of the individual from the tooth measurements.Results and Conclusions: The BLW, MDW and CL reflected significant variations among all the teeth to be effective in establishing sexual dimorphism. CA as a parameter was inadequate across all the teeth. The permanent maxillary canine was the most important tooth to be reflective of the gender and statistically significant to be utilized for gender determination.